Legal Framework To Support Islamic Banking and Finance In The United Arab Emirates - Mohamed Mashal, Mahmoud Ismaeil (Institut Agama Islam Negeri Ponorogo, 2022)
The duality of the banking system in the United Arab Emirates and its impact on economic development today represents the reality of banking systems in countries that license Islamic banking, especially with the state's first taking into account the traditional banking system. In contrast, banks, institutions, ministries, and organizations that manage work in this field practice these systems have been enabled in Muslim countries under the pressure of economic globalization. At the same time, the country is striving to develop the field of Islamic economy, support Islamic banking while enabling modern technologies and intelligent applications in the digital age, and encourage innovation in Islamic banking and finance. This trend calls for further research and deep consideration to clarify the role of the United Arab Emirates in supporting the Islamic economy and its banking and Islamic finance, as the idea of the duality of the banking system may seem contradictory in its application. As a result of this research, the Government of Dubai has started a strategic plan to develop the Islamic economy sector. The goal is to make Dubai the leading center for Islamic finance, e-commerce, the digital content industry, design and innovation, knowledge, education, and research, as well as the global reference for Islamic economy standards. The UAE government has adopted blockchain technology to implement government transactions and to achieve the desired results; the country launched the UAE Blockchain Strategy 2021m. The characteristics of the Islamic banking system reflect the reality of Sharia rulings without living and manipulation. However, the current situation has many observations, so coexistence has become at the expense of differentiation.